ADMISSION WITH ACUTE ABDOMEN: PRESENTATION, CONDITIONS IDENTIFIED AND MANAGEMENT OUTCOMES - Farzana Sabir,; Shafaq Hanif,; Fakhra Ashique,; Mohsina Saeed,; Rashida Bibi,; Sajjad Haider, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Acute abdomen is one of the few conditions that require immediate surgical intervention most of the time. However, not all cases of acute abdomen need surgery. The objective was to determine the various presentations of acute abdomen and their management outcome in patients presenting with acute abdomen to AIMS, Muzaffarabad, Azad Jammu and Kashmir, Pakistan. Methods: This prospective cohort study included individuals aged 18 and above who presented with abdominal pain lasting at least eight hours. Patients with trauma-induced abdominal pain were excluded. Consecutive non-probability sampling facilitated participant recruitment. Results: The majority (54%) were young, and males outnumbered females (62.61% and 37.39% respectively. Most patients presented within 8 hours of pain onset, diabetes and hypertension were the commonest comorbid. Mild pain was most common at presentation. In descending order, acute Appendicitis, acute cholecystitis, acute pancreatitis, intestinal obstruction, Peritonitis, UTIs, and gynaecological & obstetric conditions were the frequent reasons for abdominal pain. Conclusion: Recognizing the patterns of conditions that present as acute abdomen is essential for healthcare planners to develop effective treatment protocols, as incorrect management can lead to significant consequences.